BOTULINUM TOXIN A FOR BLEPHAROSPASM WITH DRY EYE: A SYSTEMATIC REVIEW: Poster Presentation - Observational Study - General practitioner - dr. Muthia Despi Utami; Yulia Aziza; Lukman Edwar; Made Susiyanti; Rina La Distia Nora; Ratna Sitompul (Majalah Oftalmologi Indonesia, 2023)
Introduction & Objectives : Essential blepharospasm is a neurological condition that is defined by uncontrolled and abnormal eyelid closure from a central cerebral disorder. Between 40%-85% of blepharospasm occurs in conjunction with dry eye symptoms. Botulinum neurotoxin (BoNT) injections are commonly used treatment for reducing spasms in blepharospasm. Furthermore, it is often suggested for dry eye therapy due to their ability to reduce lacrimal drainage. The purpose of this review is to assess the effectiveness of BoNT treatment for blepharospasm with dry eye symptoms. Methods : A literature research was conducted on online databases such as PubMed, Cochrane library and Google scholar. All studies of BoNT and dry eye with full-text journals published in English within the last 10 years were included. We assessed Tear Breakup Time (TBUT), Schirmer Test, and Blepharospasm Disability Index (BSDI). Results : 204 patients from 6 publications were analyzed. In five trials, the BoNT treatment statistically significant increased TBUT (p<0,5), with mean final TBUT 5,7 ±1.1 s. Furthermore, the Schirmer test also increased with the mean final score 6,29 ± 4,6 mm. The mean BSDI score dropped by 6,05 ± 3,7 in two studies. Conclusion : It is confirmed that BoNT injection is an effective treatment for essential blepharospasm with dry eye symptoms. Clinicians should be screened for dry eye in all blepharospasm patients prior to BoNT treatment.